Coping with Transition to Post-Secondary Education - Arthur, Nancy; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2011)
The increasing diversity of adult learners requires an understanding of their perceived demands and coping strategies in order to provide appropriate campus support programs. A transition perspective was used to examine the individual nature of student responses and to identify common themes in student experiences during the first year of post-secondary studies. Although academic demands were central concerns for students, there was considerable variability in the perceived characteristics of transition demands associated with the student role. Age and sex differences are discussed in light of recommendations for addressing the needs of students in transition.